Linfoma angiotrópico maligno. Com envolvimento primário do pulmão. - C Glória; N Diogo; H Vilela; D Lopes; V Lopes (Acta Médica Portuguesa, 2001)
Angiotropic malignant lymphoma (AMLy) is a rare neoplasm characterized by the intravascular proliferation of large lymphoid cells. Most of the cases reported in the literature describe a predominant involvement of the central nervous system and skin. Although any organ may be afflicted, primary involvement of the lung is unusual. We report a case of AMLy in which the pulmonary symptoms dominate the clinical picture. The tumour cells inside the small vessels of the lung were positively identified as B-phenotype lymphoid cells by immunoperoxidase stains for CD-20, which is typical of this aggressive type of lymphoma.